2014
DOI: 10.1371/journal.pntd.0002949
|View full text |Cite|
|
Sign up to set email alerts
|

Regulation of Schistosoma mansoni Development and Reproduction by the Mitogen-Activated Protein Kinase Signaling Pathway

Abstract: BackgroundProtein kinases are proven targets for drug development with an increasing number of eukaryotic Protein Kinase (ePK) inhibitors now approved as drugs. Mitogen-activated protein kinase (MAPK) family members connect cell-surface receptors to regulatory targets within cells and influence a number of tissue-specific biological activities such as cell proliferation, differentiation and survival. However, the contributions of members of the MAPK pathway to schistosome development and survival are unclear.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 53 publications
1
58
0
1
Order By: Relevance
“…A quantity of 1 μ g of total RNA was reversely transcribed with random primers, using the RevertAid First Strand cDNA Synthesis kit (Thermo Fisher Scientific, USA). As described previously , the SYBR‐Green PCR Master Mix kit (Takara, Japan) was used to measure the mRNA expression levels of TCONS_00026907, miR‐143‐5p, and ELK1. The primer sequences for GAPDH (internal control) are 5′‐CCT CGT CTC ATA GAC AAG ATG GT‐3′ (forward primer) and 5′‐GGG TAG AGT CAT ACT GGA ACA TG‐3′ (reverse primer).…”
Section: Methodsmentioning
confidence: 99%
“…A quantity of 1 μ g of total RNA was reversely transcribed with random primers, using the RevertAid First Strand cDNA Synthesis kit (Thermo Fisher Scientific, USA). As described previously , the SYBR‐Green PCR Master Mix kit (Takara, Japan) was used to measure the mRNA expression levels of TCONS_00026907, miR‐143‐5p, and ELK1. The primer sequences for GAPDH (internal control) are 5′‐CCT CGT CTC ATA GAC AAG ATG GT‐3′ (forward primer) and 5′‐GGG TAG AGT CAT ACT GGA ACA TG‐3′ (reverse primer).…”
Section: Methodsmentioning
confidence: 99%
“…Ribosome, proteasome, aminoacyl-tRNA biosynthesis and RNA transport were significantly upregulated in both groups, indicating overall higher rate of protein turnover upon exposure. In contrast, biological pathways reflecting phenotypes including neuroactive ligand-receptor interaction [regulating locomotion (Kong et al, 2015)], wnt-signaling (regulating reproduction and cell growth (Inoki et al, 2006;Hernandez Gifford, 2015) and MAPK signaling (regulating reproduction and cell growth (Zhang & Liu, 2002;Andrade et al, 2014) were significantly down-regulated in both exposures (Fig. 7).…”
Section: Resultsmentioning
confidence: 98%
“…The top 20 significant KEGG pathways identified in both exposure studies are similar to the findings based on GO BPs. In particular, the regulatory biological pathways linked to phenotypes, including neuroactive ligand-receptor interaction (relates to locomotion Inoki et al, 2016), wnt and MAPK signaling pathways (relates to reproduction and cell growth (Inoki et al, 2016;Hernandez Gifford, 2015;Zhang & Liu, 2002;Andrade et al, 2014)), were found to be downregulated in both experiments. The pathway interaction analysis by ClueGO showed that wnt signaling pathway was interacting with tgf-beta pathway which was also enriched with significantly negative NES in both toxicities.…”
Section: Discussionmentioning
confidence: 93%
“…Robust activation of the ERK1/2, p38 pathways, as well as the JNK MAPK pathway was observed in SjE16.7 stimulated macrophages. Previous work has shown that schistosome egg antigens stimulate MAPK pathways in macrophages, dendritic cells and trophoblast cells (Wang et al, 2006;Andrade et al, 2014;Ressurreicao et al, 2011), and since SjE16.7 is a protein component of schistosome eggs it is perhaps not surprising that SjE16.7 also induces MAPK activation in macrophages. RacGTPases are small signaling G proteins implicated in the control of cytoskeletal events as well as in coordinating diverse cellular functions (Bustelo et al, 2007;Pai et al, 2010).…”
Section: Discussionmentioning
confidence: 99%